Time is running out: Microsatellite data predict the imminent extinction of the boreal lynx (Lynx lynx) in France - Huvier, Nathan; Moyne, Gilles; Kaerle, Cécile; Mouzon-Moyne, Lorane (Frontiers in Conservation Science, 2023)
The presence of the Eurasian lynx in the French Jura Mountains, that has occurred in the late 1970s, is the result of the dispersion of lynxes from the Carpathian region reintroduced in Switzerland in the early 70’s. Since then, the state of this population remains poorly known. An estimation gives a number of individuals between 120 to 150 and opportunistic observation and monitoring suggest poor connectivity with the populations in Germany or in other part of Switzerland. Forty years after it come back in France, we could expect a higher number of individuals, but possible inbreeding depression as well as threats such as poaching and car collision can explain the limitation of number of individuals observed and may lead to a new extinction of the specie in this region. We have used 23 microsatellite markers and 78 DNA samples, collected between 2008 and 2020, to establish the genetic state of the French Jura Mountain lynx population. Our results showed extremely low genetic diversity with an observed heterozygosity (Ho) of 0.36 and an effective population size (Ne) of 38.2. When comparing the source population (Carpathian), the inbreeding level is of great concern (Fe = 0.41). These results are one of the lowest recorded for the Eurasian lynx. To avoid the near incoming extinction, that we are estimating, will happens in about 30 years, we recommend a rapid intervention in order to reinforce this population and find solution for a more sustainable conservation.